Quantitative flow ratio computed from invasive coronary angiography as a predictor for cardiac allograft vasculopathy after cardiac transplant - Shah, Harsh; Lee, Injoon; Rao, Sriram; Suddath, William; Rodrigo, Maria; Mohammed, Selma; Molina, Ezequiel; García-Garcia, Hector M.; Kenigsberg, Benjamin B. (The international journal of cardiovascular imaging, 2024)
Cardiac allograft vasculopathy (CAV) is a significant determinant of long-term survival in heart transplant recipients. Standard CAV screening typically utilizes invasive coronary angiography (ICA). Quantitative flow ratio (QFR) is a computational method for functional testing of coronary stenosis, and may add diagnostic value to ICA in assessing CAV. Consecutive subjects who received heart transplantation and underwent two separate routine coronary angiograms between January 2013 and April 2016 were enrolled. Coronary angiograms and IVUS were performed per local protocol at 1, 2, 3 and 5 years post-transplant. QFR was calculated offline. CAV was assessed semi-quantitively based on coronary angiogram results. Twenty-two patients were enrolled. Mean time from transplant to first included ICA was 2.1 years. QFR in at least 1 coronary vessel was interpretable in 19/22 (86%) of initial ICA (QFR1). QFR1 correlated well with the CAV score derived from the second ICA (CAV2) with a clustering of CAV at lower QFR values. In a receiver-operating characteristic (ROC) analysis, an optimal QFR threshold of 0.88 yielded 0.94 sensitivity and 0.67 specificity (AUC of 0.79) for at least non-obstructive subsequent CAV. Initial angiographically and intravascular ultrasound derived CAV severity poorly predicted subsequent CAV severity. QFR derived from invasive coronary angiography predicts subsequent development of CAV more accurately than angiography and intravascular ultrasound. This novel method of coronary flow assessment in recipients of heart transplantation may be useful to diagnose and predict subsequent CAV development.